Perencanaan Pembangunan Infrastruktur Perdesaan: Kajian Pustaka Terstruktur: Rural Infrastructure Development Planning: Structured Literature Review - Anisa Ana Fitrianti; Ach. Apriyanto Romadhan; Salahudin (P4W LPPM IPB, 2022)
This study aims to provide an understanding of village development planning in the infrastructure sector using the literature review method, which is to review and re-read the main ideas on the same topic and then add arguments and the author's views or opinions on the topic to be raised. On the other hand, by using a review system like this, authors can also see the shortcomings of previous researchers so that they can formulate and improve regularly. This research reveals that in village development planning currently, it is necessary to have an effective plan and of course produce good planning. Therefore, this study aims to provide a critical review of several articles published on Scopus and categorize themes or concepts related to the study of village development planning. Through descriptive analysis, this study uses a literature review method using VOSviewer software and produces 267 articles indexed by Scopus. Furthermore, this research deals with dominant themes such as rural area, land, rural development. The result and discussion are related to the theme of village development planning in the infrastructure sector, showing that there are 145 concepts in the study of village development planning.